Shear Strength Characteristics of Acidic-clay stabilised with Ca-based Binding Agent - ALBI, NUR ISMADIANA IZIKA; CHAN, CHEE MING; SANI, SALINA (Progress in Engineering Application and Technology, 2023)
Road mobility be in demand since it improves access to economic resources, jobs, healthcare facilities, and educational institutions. The construction of a road on acidic soil with low-strength and highly compressible soils can lead to settling and collapse issues. Construction on acidic soils with low strength can cause settlement problem and collapse on the building and roads. This has become a difficulty for engineers and the road users, who must ensure the safety and quality of the construction on this soil.  This research aims to determine the shear strength characteristics of the stabilized acidic soil with field application considerations and to formulate the optimum Fibrobase binding agent dosage for strength enhancement of acidic clay. Unconfined compression strength was the strength test employed in this investigation to evaluate the strength of treated samples, with the BS 1377: Part 7 standard serving as the reference. Acidic soil samples are treated and then allowed to cure for 3, 7, 14 and 28 days. From the analysis done in the UCS test, it can be concluded that the best mixed ratio is 5RS:5S, as it achieves high compressive stress with the optimum dosage of 4% of Fibrobase and the optimum curing period achieves the best compressive strength performance, which 2177 kPa.   In this research, the aim and the objectives have been successfully achieved in determining the shear strength characteristics. The second objective of this research was also achieved when the mixed ratio of the acidic soil reached its highest strength during the optimum curing period at 28 days with an optimum dosage of 4% of Fibrobase.